Comparison of Outcome of Desarda’s Repair with Lichenstein Mesh Repair in Inguinal Hernia - Bilal Mehmood, Muhammad Waqas Raza, Hafiza Kiran Saleem Butt, Shahid Hameed, Aqsa Nadar, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: to compare the outcomes of lichenstein mesh repair with desarda’s repair with in inguinal hernia. Methods: This randomized control trial was conducted at department of surgery (Hospital name) on 64 patients divided in two groups, group A (Desdra) and Group B (lichenstein). Primary outcomes were surgical site infection, seroma and postop pain assessment on 7th postop day. Secondary outcomes were mean hospital stay, return to work and mean operative time. Results: Desarda’s group had significantly less operative times as compared to lichenstein group 40.38±3.26 vs 45.09±3.97 (p=0.0001). SSI, seroma and recurrence of hernia in both groups were not statistically significant. Mean postop pain on 7th day, mean hospital stay and return to work was statistically significant in both groups. Conclusion: Desarda tissue-based repair, which is equally effective as the traditional Lichtenstein tension-free mesh repair, can be used to successfully repair primary inguinal hernias without mesh implantation. Keywords: Desarda’s Repair, Lichenstein Mesh Repair, Inguinal Hernia